Financial literacy and its role in achieving strategic Financial managment: An analytical study of the opinions of a sample of managers and heads of departments in private commercial banks in the governorates of (Baghdad, Holy Karbala, and Babylon). - Towfeeq Abdul Ameer, Ameer; Ahmed Fares, Ali (Iraqi Journal for Administrative Sciences, 2024)
In view of the great development taking place in the world today with regard to strategies and ways that increase competition intensity, financial institutions have realized the importance of these strategies and their role in achieving the objectives of competitive banks. Baghdad, Holy Karbala, Babylon) as well as learning about financial literacy and what is the relationship between strategic financial management and financial literacy.To achieve the foregoing, the researcher took a regular sample of (120), which included managers and heads of people in private banks, the research sample, which are (Bank of Baghdad, Khaleeji Commercial Bank, National Bank of Iraq, Investment Bank of Iraq, Credit Bank of Iraq, United Investment Bank, Middle East Bank of Iraq The researcher adopted the questionnaire as a tool for collecting data after verifying its validity and stability, and the SPSS and AMOS programs were used to extract digital indicators for the purpose of analyzing and interpreting them statistically. As for the most important conclusions reached by the researcher in his research, there is a positive correlation with statistical significance between strategic financial management and financial literacy in the research sample banks.